2006
DOI: 10.1111/j.1365-2929.2006.02561.x
|View full text |Cite
|
Sign up to set email alerts
|

The predictive validity of grade point average scores in a partial lottery medical school admission system

Abstract: The GPA of school-leaving examinations was found to be related to study success, career development and scientific performance. In this study the usual problem of restriction of range was shown to be absent. The weighted lottery procedure even resulted in an over-dispersion of candidates relative to the applicants. The resulting effect sizes were in agreement with those reported in other studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
2
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 17 publications
3
35
2
4
Order By: Relevance
“…For instance, in a study, involving more than 5,000 first-year students in six different subjects, it was demonstrated that a one point higher secondary education GPA doubled the chance of completing the first year within the allocated time frame (Jansen 2004). In a recent study of Dutch medical education, study delay was negatively related to the final examination GPA in secondary education: The lower the GPA, the more time needed to complete medical education (Cohen-Schotanus et al 2006). A difference in initial aptitude often emerges as the most important determinant of whether a student fails or succeeds (Arulampalam et al 2007;Astin 1997;Lindblom-Ylanne et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in a study, involving more than 5,000 first-year students in six different subjects, it was demonstrated that a one point higher secondary education GPA doubled the chance of completing the first year within the allocated time frame (Jansen 2004). In a recent study of Dutch medical education, study delay was negatively related to the final examination GPA in secondary education: The lower the GPA, the more time needed to complete medical education (Cohen-Schotanus et al 2006). A difference in initial aptitude often emerges as the most important determinant of whether a student fails or succeeds (Arulampalam et al 2007;Astin 1997;Lindblom-Ylanne et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The most obvious one would be variation between student cohorts. However, in this study this effect is expected to be small, because the population of medical schools in the Netherlands is quite homogeneous due to admission by national lottery procedure among students who have successfully passed their final examinations at the required level of secondary education, which is highly comparable across the board (Cohen-Schotanus et al 2006). It is important to note that for the average cumulative deviation to be a valid indicator of the relative performance of a school, it is essential that there should be no or only a negligible systematic difference in performance between the cohorts entering the schools that are compared.…”
Section: Discussionmentioning
confidence: 99%
“…35 Finally, many authors who undertake the subject of dropping out of medical studies showed no intergender differences in this area. 36,37 An indepth analysis concerning intergender differences in the achieved learning outcomes suggests that they may be conditioned by a greater conscientiousness, more diligent work during exercises, more diligent attendance in women than men. 38 However, in the context of a potential influence of gender in the students of phar macy, further studies are necessary which would provide evidence supporting the thesis that this demographic variable is important when predicting attrition.…”
Section: Discussionmentioning
confidence: 99%